Guarantee of peace the League of Nations in British policy, 1914-1925 - Yearwood, Peter J. (Oxford University Press, 2009)
This new look at the League of Nations is not an attempt to realise an idea, but as an element in the day-to-day conduct of Britain's foreign policy and domestic politics during the period 1914-25.